A comparative analysis of the burden, trends and inequalities of tracheal, bronchus, and lung cancer in India from 2000 to 2021: A systematic analysis for the Global Burden of Disease study 2021 - Shuting Rao; Haijiang Wu; Guibin Zhang; Wenli Dong; Luzhe Cui; Yashu Wang; Xinna Deng (PLoS ONE, 2025)
Background Understanding the tracheal, bronchus, and lung (TBL) cancer burden caused by tobacco exposure in India can help local governments implement targeted measures for prevention and treatment of the disease. Methods The burden of TBL cancer deaths and disability-adjusted life years (DALYs) attributable to tobacco exposure from 2000 to 2021 were presented by age, sex, and region. A Joinpoint model was used to analyze temporal trends of the disease, while decomposition analysis was conducted to quantify the contributions of population growth, aging, and epidemiological changes. In addition, the age-period-cohort (APC) model was implemented to assess the effects of age, period, and cohort on tobacco-related TBL cancer deaths and DALYs burden. Finally, age-standardized deaths and DALYs rates for TBL cancer attributable to tobacco exposure were projected through 2035. Results In 2021, Mizoram recorded the highest age-standardized rates of TBL cancer deaths and DALYs attributable to tobacco exposure, regardless of sex. Uttar Pradesh and West Bengal consistently exhibited the highest number of deaths and DALYs associated with tobacco exposure across the three age groups analyzed. Population growth and aging are the primary drivers behind the increasing burden of TBL cancer. Overall, the risk of tobacco-related lung cancer death increased with age. There are differential period and cohort effects between male and female populations. In the future, the increase in age-standardized rates of deaths and DALYs attributable to secondhand smoke exposure will be more pronounced among males. Conclusion Despite ongoing efforts to control the tobacco epidemic, the burden of TBL cancer related to tobacco remains high in India. Each state in India should adopt targeted measures based on local conditions to address the health threats posed by tobacco.